Efficient cleavage of DNA oligonucleotides by a non-FokI-type zinc finger nuclease containing one His4-type finger domain derived from the first finger domain of Sp1. Issue 19 (1st October 2015) - Negi, Shigeru; Yoshioka, Michiko; Mima, Hiroko; Mastumoto, Makoto; Suzuki, Michiko; Yokoyama, Mao; Kano, Koji; Sugiura, Yukio
Graphical abstract: Abstract: In this study, we sought to improve the hydrolytic activity of a His4 -type single finger domain (f2), which was previously derived from the second finger domain (f2′) of the Sp1 zinc finger protein (Sp1wt), which has 3 tandem finger domains (f1′, f2′, and f3′). To this end, 2 His4 -type single finger domains were generated by mutating 2 Cys residues participating in Zn(II) coordination with the His residues in the first (f1′) and third finger (f3′) domains of Sp1wt. Circular dichroism spectroscopy results showed that the first and second His4 -type zinc finger domains (f1 and f2) adopted folded ββα structures in the presence of Zn(II), but that the third His4 -type zinc finger domain (f3) did not. Non-FokI-type zinc finger nucleases containing 3 or 4 finger domains were also prepared by combining a His4 -type zinc finger domain with the Sp1wt scaffold. We studied their DNA-binding abilities and hydrolytic activities against DNA oligonucleotides by performing gel-mobility-shift assays. The results showed that f1 had higher hydrolytic activity for a DNA oligonucleotide with a GC box (5′-GGG GCG GGG-3′), compared with that of f2, although both His4 -type single finger domains had similar DNA-binding affinities. The difference in the hydrolytic activity between f1 and f2 was ascribed not only to the zinc coordinate structure, but also to its folding structure and the stability of finger domain.